The Effect of Self-Efficacy and Creative Work Climate on Knowledge Sharing Among Teachers in Cirebon City - Tri Astuti; Diana Maya (Universitas KH. Abdul Chalim Mojokerto, 2025)
Self-efficacy and creative atmosphere influence knowledge growth. This study examines how self-efficacy and creative atmosphere influence knowledge. The quantitative research method used a survey of academic and professional respondents. The data was processed by utilizing regression methods and path analysis to determine the relationship between the variables studied. The findings of this study reveal that a number of factors such as personal experience, social support, and a conducive work or learning environment have a significant influence on self-efficacy. Meanwhile, leadership factors, organizational culture, and available facilities play a role in creating a positive creative climate. In addition, self-efficacy and creative climate directly impact on increasing knowledge sharing and innovation in various fields. These findings confirm that strengthening self-efficacy and creating a supportive creative climate are essential in knowledge development, both in the context of education and the world of work.